Devising a scientific-methodical apparatus for the appropriate distribution of damaged weapons among specialized repair and restore units - Maistrenko, Oleksandr; Khoma, Vitalii; Kurban, Volodymyr; Rakhmanyi, Oleksandr; Shvets, Mykola; Stehura, Serhii; Horbenko, Serhii; Pochynok, Serhii; Isenko, Vitaly; Kuznetsov, Valeriy (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the process of distribution of damaged weapons and military equipment of various types among specialized repair and restoration units. The problem being solved is the lack of adaptability of the existing scientific and methodical apparatus to the expedient distribution of damaged weapons and military equipment of various types among specialized repair and restoration units. An algorithm for the expedient distribution of damaged weapons and military equipment among specialized repair and restoration units is proposed, which is based on the method of non-linear programming (the method of two functions). The essence of the developed algorithm is to take into account the non-linearity of objective functions of both the consumer and the resource. A feature of the developed algorithm of expedient distribution is taking into account the heterogeneity of both damaged weapons and military equipment, as well as the specificity of repair and restoration units. The scope of practical application of the proposed algorithm is management processes in military hostilities during combat operations. The procedure for appointing specialized repair and restoration units for the restoration of damaged weapons and military equipment has been improved. The peculiarity of the proposed procedure is that it is based on the distribution of damaged weapons and military equipment not only on the basis of the capacity of certain repair and restoration units but also taking into account their compliance. The specified procedure makes it possible to select those repair and restoration units that could allow for an increase in the level of restoration of damaged weapons and military equipment by 20 %. The scope of practical application of the improved procedure is the management processes of the technical support system of troops when planning measures to restore damaged weapons and military equipment